The Implementation of Regional Regulation No. 3 of 2023 in Managing the Distribution of Palm Wine (Tuak) in Indragiri Hilir Regency - Ryandi Aditya; Adil Mubarak (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Traditional alcoholic beverages, especially tuak, remain a governance concern in Indragiri Hilir Regency because their circulation is closely connected with public order, social stability, and community protection. To respond to this issue, the local government issued Regional Regulation Number 3 of 2023 concerning Public Order, Public Peace, and Community Protection. This article analyzes how the regulation is carried out in controlling tuak circulation in Tembilahan District and identifies the conditions that influence its effectiveness. This research applied a descriptive qualitative method. Information was obtained through in-depth interviews, field observations, and document analysis involving Satpol PP officers, community figures, teachers, youth representatives, residents, and tuak sellers. The collected data were analyzed through data reduction, organized data presentation, and verification of conclusions. The findings indicate that Regional Regulation Number 3 of 2023 has not yet been implemented optimally. Its effectiveness is still limited by several obstacles, including policy dissemination that has not reached all groups, restricted human and operational resources, uneven enforcement practices, and weak coordination among related institutions. Strengthening public education, institutional capacity, supervision, enforcement, and collaboration between government agencies and community actors is therefore necessary. This study enriches the discussion of public policy implementation in local contexts, particularly policies aimed at managing social problems and maintaining public order.